Foamed structured packing for mass-transfer equipment produced by an innovative 3D printing technology. (12th October 2022) - Flagiello, D.; Tammaro, D.; Erto, A.; Maffettone, P.L.; Lancia, A.; Di Natale, F.
Graphical abstract: Highlights: Novel packing manufacture using 3D printing technology combined with foaming technology. Tailor-made design of structured packing in-situ with zero transport energy/emissions. Enhancing surface area (greater than20%) and weight reduction (greater than40%) of packing thanks to foaming. Enhanced mass-transfer for 3D packing as compared to commercial packing. Process intensification of Flue-Gas Desulphurization (FGD) wet-scrubbing. Abstract: Packed columns are largely adopted for multi-phase reactors and separators, i.e., distillation, production or purification of commercial products, flue-gas treatment, conditioning and requalification of air for indoor systems, and cooling of industrial waters. In this work, we report the results of a first experimental study on the pressure drops and the mass transfer rates of an innovative 3D foam-printed packing that has the advantages to be light, cost effective, and easy-to-produce. The physical properties of the 3D foam-printed packing are characterized in terms of density, wettability, and surface roughness. Subsequently, the packing is tested in a pilot-scale flue-gas desulphurization (FGD) plant using tap water to estimate the pressure drops in dry and wet conditions and the overall mass transfer rate for a typical absorption experiments, largely adopted for packing characterization. The results show that the new packing has slightly higher mass transfer efficiency and pressure drops than other similar commercial packing in the same ranking range of nominal surface area. A comparison with former experiments with state-of-art Mellapak 250X in Hastelloy, tested in our previous works with the same experimental setup, show that the improvement in mass transfer rate overwhelms the increase of pressure drops, so that the overall performances of the new packing on for FGD applications appeared as more convenient than the Mellapak 250X packing, in the investigated conditions. The experimental results are explained in terms of the superficial properties of the packing, in particular: both pressure drops and mass transfer rate data can be correlated with the morphology of the packing surface roughness, in turn both deriving from the printing and the foaming processes, and the larger thickness of the sheet. Besides, the same printing material has higher wettability than the Mellapak 250X in Hastelloy, improving the liquid distribution on the packing surface. Finally, they are probably influenced by a new mechanical design of baffles, which reduces liquid maldistribution. The overall performance and the production process advise for further investigations on the use of 3D foam-printed packings for large-scale industrial units.